Plasmalyse - A Novel Plasma Sterilization System for Dental and Medical Applications - Villeger, Sandrine; Ricard, André (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
Reactors for medical instrument sterilization were studied by starting from 5-liters to 17-liters volumes for dental applications. The first challenge was to find low-cost elements to obtain a prize in the same order as a commercial autoclave. For that, a microwave source from a commercial microwave oven and the small vacuum pump of the autoclave were tested to build up a new plasma sterilizator, named Plasmalyse. Sterilization of 6 Log (10-6 spores survivors) was obtained after a treatment of 7 minutes at 100°C and 120 minutes at 30°C in comparison to 40 minutes at 105°C with the commercial autoclave. After that, Plasmalyse was transformed for the Hospital application, with a 135 liters reactor, connected to 4 microwave sources and with an efficient vacuum pump, to obtain a 6 Log spores inactivation at 60°C in a treatment time of 20 minutes. Moreover, the N-atom transmission and E-coli inactivation through hollow tubes were studied.